On-Farm Evaluation of Front Line Demonstrations on Mustard in Eastern Plain Zone of Uttar Pradesh (Indian Journal of Extension Education, 2012)
Rapeseed-Mustard is an important oilseed crops and contributes around 23.2 per cent of total oilseed production in India. It is pivotal in supplementing the income of small and marginal farmers of adjoining district of Varanasi i.e. Eastern Plain Zone of Uttar Pradesh. One of the major constraints of traditional mustard farming is low productivity due to non adoption of improved high yielding varieties and recommended package of practices, Front-line demonstrations in farmers fields were conducted which comprised of cultivation practices such as use of improved high yielding varieties, line sowing, balanced application of fertilizers specially inclusion of sulphur and control of mustard aphid through insecticide at economic threshold level. The study revealed that the yield of mustard ranged from 8.0 per cent to 22.15 per cent over local check (Varuna) during the course of study during 2006-07 to 2008-09 (3 years). However, the technology gap of 8.21 q/ha as minimum during 2006-07 to maximum of 10.14 q/ha (2008-09) shows the gap in demonstration yield over potential yield. Hence increase in yield over farmers yield was evident which indicated the need of educating farmers through frontline demonstration.